Predicting the Success of Emergency Surgical Treatment of Acute Massive Pulmonary Embolism Based on the Results of Multislice Computed Tomography - T. N. Trofimova; M. B. Sukhova (Вестник рентгенологии и радиологии, 2020)
Objective – to assess the informativeness of multisclice computed tomography (MSCT) angiopulmonography in the assessment of peripheral blood flow and to determine the prognostic role of angiographic massiveness and volume of preserved peripheral blood flow as predictors of success of emergency surgical treatment of acute massive pulmonary embolism (PE). Material and methods. The article presents the results of 7-year work for the period from March 2012 to September 2019, which included a pilot retrospective stage (analysis of the results of 264 MSCT procedures with contrast enhancement for acute PE in patients aged 32 to 69 years for the period 2012–2013) and prognostic practical work (the second stage, analysis of the results of 974 MSCT procedures with contrast enhancement in patients aged 25 to 78 years for the period 2013–2019).Results. The obtained results and statistical dependences proved the influence of the saved volume of peripheral arterial pulmonary blood flow on the outcome of surgical treatment. The use of this indicator as an MSCT predictor reduced the hospital mortality rate from 7.2% to 3.5%. The analysis of the influence of the initial angiographic massiveness of PE on the outcome of surgical treatment has not been confirmed.Conclusion. According to the results of the study, we recommend the inclusion of segmental arterial pulmonary blood flow analysis by MSCT with contrast enhancement in the algorithm of preoperative examination of patients with acute massive pulmonary embolism in case of emergency surgical treatment.